2016
DOI: 10.1002/cam4.811
|View full text |Cite
|
Sign up to set email alerts
|

Candidate microRNAs as biomarkers of thyroid carcinoma: a systematic review, meta‐analysis, and experimental validation

Abstract: Thyroid cancer is one of the most common carcinomas of the endocrine system with an increasing incidence. A growing number of studies have focused on the diagnostic and prognostic values of dysregulated microRNAs (miRNAs) in thyroid carcinoma. However, differences in the measurement platforms, variations in lab protocols, and small sample sizes can make gene profiling data incomparable. A meta‐review of the published studies that compared miRNA expression data of thyroid carcinoma and paired normal tissues was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 53 publications
1
27
0
1
Order By: Relevance
“…It has been shown that let-7a and miR-345 (both 5p microRNAs) are downregulated in DICER1-related goiter, compared to normal thyroid tissue (6). Moreover, low levels of let-7 and miR-345 have been recurrently found in thyroid tumors (32,36). After the induction of hyperplasia, DICER1 'hotspot' mutations in RNase IIIb may occur on the other allele (as observed in the proband, individual I-4 and individual III-2), giving rise to cell clones that would develop into thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that let-7a and miR-345 (both 5p microRNAs) are downregulated in DICER1-related goiter, compared to normal thyroid tissue (6). Moreover, low levels of let-7 and miR-345 have been recurrently found in thyroid tumors (32,36). After the induction of hyperplasia, DICER1 'hotspot' mutations in RNase IIIb may occur on the other allele (as observed in the proband, individual I-4 and individual III-2), giving rise to cell clones that would develop into thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of extremely conserved non‐protein coding RNAs, which could regulate gene expression at a posttranscriptional level . Mounting evidence has shown that numerous miRNAs are dysregulated in tumor, contributing to the tumorigenesis and development of almost all cancer, including osteosarcoma . For instance, miR‐1 and miR‐133b were downregulated in osteosarcoma and may control cell proliferation and cell cycle .…”
Section: Introductionmentioning
confidence: 99%
“…15,26,27 Although PIK3CA and PTEN mutations have been reported in follicular thyroid cancer, poorly differentiated thyroid cancers, and anaplastic thyroid cancer, [28][29][30] they can also be found in benign thyroid adenomas, as can GNAS and ALK mutations and THADA-and PPARG-related fusions. [46][47][48][49][50] A multiplatform approach using a combination of a mutation panel and a microRNA risk classifier has been shown to effectively "rule-in" and "rule-out" high risk of malignancy with results being predictive of surgical treatment decisions that are appropriately aligned with cancer risk. 15 Although the predictive value for malignancy of these oncogenic changes is not well understood when found individually, it is well established that coexistence of many of these oncogenic changes along with other oncogenic drivers is generally associated with aggressive forms of thyroid cancer and poor prognosis.…”
mentioning
confidence: 99%